THE INTEGRATION OF GREEN-BUILDING TASKS AND PROJECT-DESIGN PROCESSO - CASE STUDY - Orsi, Alessandro; Armiñana, Eugenio Pellicer (Mix sustentável, 2018)
The development of a green-building project following a specific reference standard such as LEED, brings new conditions and restrains for all subjects involved in the process. Such changes affect technicians, owners, bureaucracy and also the management tasks either during design or construction phases.  Within this scope, the management of sustainabilityrelated activities plays a key role for the optimization of the design-project development. This research analyzes the design process of two different case-study projects undergoing the same green-building certification from the project management perspective. In both project sustainability-related activities were performed throughout the design process however, in one of them such activities were integrated to the building-design development and in the other they were not.  A new methodology was created in order to analyze the project and evaluate the effects of detected projectmanagement issues under three different points of view: costs, time and building sustainability. Such “issues” were identified by researchers on the basis of the LEANdefinition of “waste”.  The results showed that integration of green-building tasks through the development of the design process can considerably affect the cost, schedule and sustainability of the project design.